Evaluation of clinically significant adverse events in patients discharged from a tertiary-care emergency department in Taiwan. Issue 3 (20th March 2012) - Wang, Lee-Min; How, Chorng-Kuang; Yang, Ming-Chin; Su, Syi; Chern, Chii-Hwa
Abstract : Objective: To investigate the reasons for the occurrence of clinically significant adverse events (CSAEs) in emergency department-discharged patients through emergency physicians' (EPs) subjective reasoning and senior EPs' objective evaluation. Design: This was a combined prospective follow-up and retrospective review of cases of consecutive adult non-traumatic patients who presented to a tertiary-care emergency department in Taiwan between 1 September 2005 and 31 July 2006. Data were extracted from 'on-duty EPs' subjective reasoning for discharging patients with CSAEs (study group) and without CSAEs (control group)' and 'objective evaluation of CSAEs by senior EPs, using clinical evidences such as recording history, physical examinations, laboratory/radiological examinations and observation of inadequacies in the basic management process (such as recording history, physical examinations, laboratory/radiological examinations and observation) as the guide'. Subjective reasons for discharging patients' improvement of symptoms, and the certainty of safety of the discharge were compared in the two groups using χ 2 statistics or t test. Results: Of the 20 512 discharged cases, there were 1370 return visits (6.7%, 95% CI 6.3% to 7%) and 165 CSAEs due to physicians' factors (0.82%, 95% CI 0.75% to 0.95%). In comparisons between the study group and the control group, only some components of discharge reasoning showed a significant difference (p<0.001). Inadequacies in the basic management process were the main cause of CSAEs (164/165). Conclusion: The authors recommended that EP follow-up of the basic management processes (including history record, physical examination, laboratory and radiological examinations, clinical symptoms/signs and treatment) using clinical evidence as a guideline should be made mandatory.